[About CEU - Part 3]
Continuation of the series “About CEU.” Contains interviews with a professor and a student from the Department of Gender Studies as well as recordings from a lecture on constitutional issues and electoral processes held by Professor András Sajó. The lecture is followed by an interview with Prof. András Sajó who earlier that year won the “Best Professor Award”. A student attending his class explains why CEU is a valuable choice and what would be her future prospects with such an academic background. Presentation of American poet and novelist Michael Blumenthal (editor at the CEU Press between 1992-1996) while promoting the book “When History Enters the House: Essays from Central Europe” is also recorded on this tape. This event is followed by an interview with cofounder and co-director of the Program on Gender and Culture at Central European University between 1996-1998, Kim Lane Scheppele. The recordings end with an interview about the CEU Bookstore.